PERAN KEPALA SEKOLAH SEBAGAI FASILITATOR DALAM PENGEMBANGAN MINAT DAN BAKAT PADA PROGRAM EKSTRAKURIKULER DI SMPN 1 TANJUNG JABUNG BARAT - Fahrezi, Muhammad Dimas; Muspawi, Mohamad; Musyaiyadah, Musyaiyadah (STKIP Pesisir Selatan, 2025)
The success of extracurricular activity management is largely determined by the principal's leadership. The principal not only serves as a policy administrator but also as a key actor in mobilizing all school resources to ensure the effective and sustainable running of extracurricular activities. One of the principal's strategic roles is as a facilitator, ensuring the availability of facilities, infrastructure, policy support, and access to internal and external school resources. The development of students’ interests and talents through extracurricular activities is an integral part of education oriented toward character building and non-academic skills, in which the success of implementation is strongly influenced by the school principal’s leadership as a facilitator. This qualitative case study describes the principal’s role, challenges, and solutions in developing students’ interests and talents through extracurricular activities at SMP Negeri 1 Tanjung Jabung Barat using interviews, observations, and documentation analyzed with the Miles and Huberman interactive model. The findings indicate that the principal actively facilitates extracurricular activities through the provision of facilities, policy support, and coordination with teachers, while addressing limitations in facilities, budget, and teachers’ workload through adaptive and contextual leadership strategies.